Experimental Study on Preparation and Performance of Concrete With Large Content of Fly Ash - Li, Changyong; Geng, Haibin; Zhou, Siyi; Dai, Manman; Sun, Baoshan; Li, Fenglan (Frontiers in Materials, 2022)
With the increasing attention to the environment protection and recycle of solid waste, the comprehensive utilization of fly-ash in building composites has been an issue of great concern. In this paper, the fly-ash concrete (FAC) with the content of fly-ash no less than 50% in total weight of binders was developed. The activity of fly-ash was firstly detected while the water requirement of normal consistency and the setting time of cement fly-ash paste were examined. The strengths of cement fly-ash mortar at curing age of 7 days and 28 days were determined, the factors of water to binder ratio from 0.3 to 0.5, the content of fly-ash from 40% to 80% and the excitation measures with additional Ca(OH)2 and steam curing at initial were considered. After that, the FAC was designed by using the replacement of cement with excessive fly-ash to reduce the water to binder ratio, the water-to binder ratio reduced from 0.50 to 0.26, and the content of fly-ash varied from 52% to 60%. Results show that a reduction of the water requirement of normal consistency and an elongation of the setting time took place with the content of fly-ash increased from 40% to 80% for the cement fly-ash paste; the low strength of cement fly-ash mortar directly related to the slow reaction of fly-ash with hydration product Ca(OH)2 of cement or additional Ca(OH)2, steam curing at initial 24 hours benefited to the activity excitation of fly-ash which con-tributed to the early strength of cement fly-ash mortar. The water to binder ratio of FAC reduced by the re-placement of cement with excessive fly-ash did not affect the workability of fresh mix, the axial compressive strength and the modulus of elasticity of FAC reached the predicted values at curing age of 28 days, while the tensile strength was lower than predicted. When the curing age was at 56 days, all the basic mechanical properties of FAC satisfied the prediction. The resistances of FAC to chloride ion penetration and carbonization were realized at very high level as specified in codes.